Simulation and control of a large scale urban traffic network - Abdul Maliki Abdul Gani (2017)
The basis of this project was to analyse the effectiveness and performance of a proposed traffic scheduling strategy, a novel model which is still being developed. As traffic jams becomes more of a problem due to high volume of vehicles, new methods to ease congestion need to be designed in order to tackle this problem as part of a new Intelligent Traffic Systems. VISSIM will mostly be used in creating a network model for the scheduling strategy to be implemented. The algorithm will then be implemented in VISSIM by using MATLAB through the COM interface feature, which allows for real time data collection and calculations of the network. Afterwards, there will be discussions of the performance of the algorithm in a simple 3 by 3 network, where preliminary results show promise. Finally, there will be a conclusion and thoughts on the future work of this project.